Bilinguismo luso-alemão: a percepção de vogais alemãs por remigrantes portugueses - Flores, Cristina (2010)
This study investigates the perception of German vowels by a group of eight Portuguese adolescents and young adults who were raised bilingually in Germany and returned to Portugal in early childhood. All the participants reported that they never use German in Portugal and that they are unable to formulate accurate sentences in that language. Our aim was to test whether their perceptual ability to discriminate German sounds had undergone attrition or remained invulnerable to the lack of language use. Unlike German vowels, Portuguese vowels are not distinctive in duration and the Portuguese inventory does not contain front rounded vowels. Thus, we tested the participants’ perceptual ability to discriminate vowels in terms of duration and quality by means of a categorical discrimination test. The results reveal that the returnees were able to make vowel duration and quality perceptual distinctions in the attrited language. This indicates that their ability to discriminate German sounds seems to remain stable.